Evaluación de bioinsecticidas para el control de la mosca de la fruta (ceratitis capitata), en condiciones de laboratorio. - Yauli Zapata, Jadira Alexandra (2020)
The research was carried out in the Canton Latacunga, in Salache sector in the Entomological Laboratory of the Technical University of Cotopaxi, with the objective of evaluating Bio insecticides for the control of fly fruit (Ceratitis capitata) under laboratory conditions. So that, it was applied an entire randomized experimental block design, with 7 treatments and 3 repetitions giving a total of 21 experimental units. The methodology used was to build the appropriate experimental units to handle the trial without difficulties, then the Bio insecticides were prepared each with their two concentrations at 25% and 50%, the specimens were counted to place 200 flies for each unit experimental which lasted about two hours. After placing the 200 flies in all the boxes, the sponges were placed on a Petri dish inside the glass box, in each sponge was introduced 15cc of Bio insecticide. The first data collection was done after one hour of applying the Bioinsecticide, which took a time of 10 minutes to count dead flies and take them out of the box, then it took again the time of one hour to continue with the same process during the period of 4 hours. The research expressed the following results: the best Bio insecticide was Cicuta (Conium maculatum) with an average of 96.33 dead individuals being the one with the best control. Respectively, Tukey test at 5% for the best bio insecticide Concentration, it was 50% with an average of 98.89 dead flies being the one that obtained the best control, in the same way for the second hour with an average of 41.33 flies dead. For the interaction of the B * C factors, the greatest control was the bio insecticide of False tobacco (Nicotina glauca) with a concentration of 50% with an average of 115 dead flies during the first hour and in the same way for the second hour with an average of 54 dead flies, and during the third and fourth hour there is no statistical significance of the data taken. In the economic analysis the costs of bio insecticides are lower than the commercial compound which belong to the chemical group spinosin